2018
DOI: 10.1590/1678-4685-gmb-2017-0074
|View full text |Cite
|
Sign up to set email alerts
|

Skull shape and size variation within and between mendocinus and torquatus groups in the genus Ctenomys (Rodentia: Ctenomyidae) in chromosomal polymorphism context

Abstract: We tested the association between chromosomal polymorphism and skull shape and size variation in two groups of the subterranean rodent Ctenomys. The hypothesis is based on the premise that chromosomal rearrangements in small populations, as it occurs in Ctenomys, produce reproductive isolation and allow the independent diversification of populations. The mendocinus group has species with low chromosomal diploid number variation (2n=46-48), while species from the torquatus group have a higher karyotype variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…The hypothesis of the leading role of chromosomal evolution in Ctenomys [ 45 ] was not supported by mtDNA and microsatellite data. Attempts to find a correlation between morphological and chromosomal variability in Ctenomys have also not been successful [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis of the leading role of chromosomal evolution in Ctenomys [ 45 ] was not supported by mtDNA and microsatellite data. Attempts to find a correlation between morphological and chromosomal variability in Ctenomys have also not been successful [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the evidence provided by molecular data sets used in this study, it is suggested that C. talarum and C. pundti complex could be considered as the same biological species, or lineages going through a recent or incipient differentiation process. To confirm any of these hypotheses, a multidisciplinary approach will be necessary, such as a study of the type material of each species (Stolz et al, 2013;Tammone et al, 2016;Sánchez et al, 2019), deep chromosome studies (Castilho et al, 2012;Kubiak et al, 2020), wider multi-locus/genomic analyses (MacManes et al, 2015;Lopes et al, 2020), environmental and ecological features (Kubiak et al, 2017;Lopes et al, 2020), and mainly exhaustive approaches on phenotypic variation at different levels (Freitas et al, 2012;Gonçalves, 2021), in conjunction with complex and deeper morphometric analyzes that integrate classical and geometric morphometry (Borges et al, 2017;Fornel et al, 2018;Leipnitz et al, 2020).…”
Section: Populations Of Talarum Groupmentioning
confidence: 99%
“…In addition, remarkable morphological homogeneity is frequent even among long-standing differentiated species (D'Elía et al 2021). In such a still largely inconclusive scenario, however, major systematic and phylogenetic knowledge has been generated in just over two decades (e.g., Lessa and Cook 1998;D'Elía et al 1999;Mascheretti et al 2000;Slamovits et al 2001;Castillo et al 2005;Parada et al 2011;Gardner et al 2014;Bidau 2015;Freitas 2016Freitas , 2021Caraballo and Rossi 2018;Fornel et al 2018;Leipnitz et al 2020;Teta and D'Elía 2020;D'Elía et al 2021;De Santi et al 2021). One of the most significant advances is the recognition of informal groups of species based on increasingly well-supported clades (Parada et al 2011;Freitas et al 2012;Gardner et al 2014;Caraballo and Rossi 2018;Londoño-Gaviria et al 2018;Leipnitz et al 2020;De Santi et al 2020, 2021Carnovale et al 2021).…”
Section: Introductionmentioning
confidence: 99%